Vitale Mystik Formen und Rezeptionen mystischen Schreibens in der Lyrik von Anna de Noailles, Ernestina de Champourcin und Antonia Pozzi - Haase, Jenny (MIMESIS, 2022)
This study examines the form and reception of mystical writing in poetry by A. de Noailles (France, 1876-1933), E. de Champourcin (Spain 1905-1999), and A. Pozzi (Italy, 1912-1938) from the perspective of current transsecular approaches, cultural studies mysticism research, and feminist literary studies.